2010
DOI: 10.1002/cjoc.201090260
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydrogenation of Cyclic N‐Sulfonylimines with Phosphine‐Free Chiral Cationic Ru‐MsDPEN Catalysts

Abstract: Phosphine-free chiral cationic Ru/diamine complexes are effective catalysts for the asymmetric hydrogenation of a range of cyclic N-sulfonylimines, affording chiral sultam derivatives with good to excellent enantioselectivity (up to 94% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Recently, Fan and co‐workers demonstrated that η 6 ‐arene/TsDPEN‐Ru II complexes, such as 43 b , 44 , and 45 , were outstanding catalysts for asymmetric hydrogenation of 2‐substituted and 2,3‐disubstituted quinolines,36a,b,d,e 2‐substituted and 2,3‐disubstituted quinoxalines,36f 2,4‐disubstituted 1,5‐benzodiazepines,36i N ‐alkyl ketimines,36g,j cyclic N‐ alkyl imines,36h and cyclic N ‐sulfonylimines,36c affording the corresponding biologically and chemically important chiral amines with excellent enantioselectivities in high yields (Scheme ) 37. Mechanistic studies on the hydrogenations of quinolines revealed that the reduction involves a reaction sequence of 1,4‐hydride addition, isomerization, and 1,2‐hydride addition (Scheme ) 36a,d.…”
Section: Mnh Catalysismentioning
confidence: 99%
“…Recently, Fan and co‐workers demonstrated that η 6 ‐arene/TsDPEN‐Ru II complexes, such as 43 b , 44 , and 45 , were outstanding catalysts for asymmetric hydrogenation of 2‐substituted and 2,3‐disubstituted quinolines,36a,b,d,e 2‐substituted and 2,3‐disubstituted quinoxalines,36f 2,4‐disubstituted 1,5‐benzodiazepines,36i N ‐alkyl ketimines,36g,j cyclic N‐ alkyl imines,36h and cyclic N ‐sulfonylimines,36c affording the corresponding biologically and chemically important chiral amines with excellent enantioselectivities in high yields (Scheme ) 37. Mechanistic studies on the hydrogenations of quinolines revealed that the reduction involves a reaction sequence of 1,4‐hydride addition, isomerization, and 1,2‐hydride addition (Scheme ) 36a,d.…”
Section: Mnh Catalysismentioning
confidence: 99%
“…The reduced products were obtained with modest to good enantioselectivities (Scheme 79). 255 6.3.2. Rh-Catalyzed Asymmetric Hydrogenation.…”
Section: Asymmetric Hydrogenation Of Cyclic Vinyl Sulfonesmentioning
confidence: 96%
“…The earliest asymmetric hydrogenations of cyclic 2-alkyl-substituted cyclic benzosulfimides S84 were reported using Ru–BINAP catalysts . However, this methodology was quickly supplanted by Ru-catalyzed asymmetric transfer hydrogenation based on TsDPEN-type ligands. For example, Fan and co-workers subjected 2-aryl/alkyl-substituted cyclic benzosulfimides S84 to hydrogenation using complex [RuOTf­(( R , R )-MsDPEN)­( p -cymene)] (Ru– L32 ). The reduced products were obtained with modest to good enantioselectivities (Scheme ).…”
Section: Synthesis Of Chiral Cyclic Sulfanes Sulfones and Sulfamidesmentioning
confidence: 99%
“…Asymmetric transfer hydrogenation of 1-phenyl dihydroisoquinolines [18], represents a considerable challenge since the catalyst bearing the ligand of N-p-toluenesulfonyl-1, 2-diphenylethylenediamine (TsDPEN) failed to catalyze this reaction under standard reaction conditions. Although the original Noyori-type ATH catalysts always bore N arylsulfonyl as the substituent, several studies showed that Ir and Ru catalysts, containing methanesulfonyl-DPEN (MsDPEN), hydrogenated various aryl-N-benzyl imines, N sulfonylimines and aryl ketones with molecular hydrogen [5,15,[19][20][21]. The ligand of methanesulfonyl DPEN is a part of a rather small group of ligands finding their use as a component of catalysts applicable for asymmetric (transfer) hydrogenation.…”
Section: Asymmetric Transfer Hydrogenation Of 1-phenyl Dihydroisoquinmentioning
confidence: 99%